Warren and Bill : Gates, Buffett, and the friendship that changed the world - McCarten, Anthony, 1961- (HarperCollins Publishers, 2024)
"Few friendships have had such far-reaching implications for the world, from finance to technology to philanthropy, as that between Bill Gates and Warren Buffett. After meeting at a party in 1991, the two played cards and golf, shared jokes, swapped trade secrets, ate junk food, talked and listened. The growing friendship would affect each man and lead to change on a grander scale, culminating in the development of the Bill & Melinda Gates Foundation, one of the largest charitable foundations in the world."--inside book cover